IMPLEMENTATION OF DIGITAL TOOLS IN CLASSROOM ACTIVITIES - Zokirova Nigorakhon Sokhiblon qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This study explores the structured integration of digital tools in language classroom activities. It highlights the use of platforms such as Duolingo, Quizlet, Wordwall, YouTube, Google Docs, and Zoom to support the development of all core language skills. The findings demonstrate that purposeful use of technology enhances student engagement, motivation, and interaction. Additionally, digital tools promote learner autonomy, collaborative learning, and continuous practice beyond the classroom. Overall, the study confirms the effectiveness of technology in creating a more interactive and student-centered learning environment.